KODE ETIK PROFESI KONSELING SERTA PERMASALAHAN DALAM PENERAPANNYA - Eko Sujadi (Tarbawi : Jurnal Ilmu Pendidikan, 2018)
Every individual is required to be able to adjust to changes that occur. For individuals who are not able to adjust to the changes, it can cause problems for them. This conditions provides great opportunities for counselors to organize counseling services. Counselors are supposedly able to apply the code of conduct in providing services to clients. Various issues of implementing the code of conduct are occurring in the implementation of counseling services, whether it is caused by counselor or external parties. Therefore, counselor should cultivate self-awareness to carry out a duty correctly, continue to improve the competence, as well as policy makers should formulate clear regulations and properly accompanied by supervision.